Late post-treatment radiographic changes 3 years following chemoradiation for glioma: the importance of histopathology. (July 2017) - Galante, Joao R; Rodriguez, Fausto; Grossman, Stuart A; Strowd, Roy E
Treatment-related changes can mimic brain tumor progression both clinically and radiographically. Distinguishing these two entities represents a major challenge in neuro-oncology. No single imaging modality is capable of reliably achieving such distinction. While histopathology remains the gold standard, definitive pathological criteria are also lacking which can further complicate such cases. We report a patient with high-grade glioma who, after initially presenting with histopathologically confirmed pseudoprogression 10 months following treatment, re-presented 3 years following concurrent chemoradiation with clinical and radiographic changes that were most consistent with progressive disease but for which histopathology revealed treatment effects without active glioma. This case highlights the potential late onset of treatment-related changes and underscores the importance of histopathologic assessment even years following initial therapy.